Monitoring and Modelling the Trends of Primary and Secondary Air Pollution Precursors: The Case of the State of Kuwait - S. M. Al-Salem; A. R. Khan (International Journal of Chemical Engineering)
Since the beginning of the industrial revolution, processes of different scales have contributed greatly to the pollution and waste load on the environment. More specifically, airborne pollutants associated with chemical processes have contributed greatly on the ecosystem and populations health. In this communication, we review recent activities and trends of primary and secondary air pollutants in the state of Kuwait, a country associated with petroleum, petrochemical, and other industrial pollution. Trends of pollutants and impact on human health have been studied and categorized based on recent literature. More attention was paid to areas known to researchers as either precursor sensitive (i.e., nitrogen oxides (NOx), volatile organic compounds (VOCs)) or adjacent to upstream- or downstream-related activities. Environmental monitoring and modelling techniques relevant to this study are also reviewed. Two case studies that link recent data with models associated with industrial sectors are also demonstrated, focusing mainly on chemical mass balance (CMB) and Gaussian line source modelling. It is concluded that a number of the monitoring stations and regulations placed by the Kuwait Environment Public Authority (KUEPA) need up-to-date revisions and better network placement, in agreement with previous findings.